INTEGRATION OF INFORMATIONAL COMPUTER TECHNOLOGIES SMK: AUTOMATION IN RATING OF THE MAIN RAW MATERIALS - S. A. Pavlenko (Литьë и металлургия)
Decrease of calculations variability due to centralized automation of engineering processes enables to receive effective results from rating of the raw materials consumption.